Asuhan Kebidanan Komprehensif pada Ny. N Umur 31 Tahun dengan Kekurangan Energi Kronik di PMB Ny.S di Wilayah Kerja Puskesmas Kaliwadas Tahun 2023 - Mahalia Tiara Suci; Himatul Khoeroh; Surniah Surniah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
MMR (WHO) in 2022 will reach 91.46/100,000 live births. MMR in Indonesia (2021) 7,389/100,000 KH. Brebes MMR in (2021) is 105 cases and IMR is 259 cases in 2022. Data from the Kaliwadas Health Center in (2022) is 1 case and IMR (2022) is 0 cases. In WHO (2021), there are (73.2%) pregnant women with CED. And in Bebes there will be 64 cases of pregnant women with Chronic Energy Deficiency (KEK) in 2022. Objective: To provide comprehensive care for pregnant women, giving birth, newborns, postpartum and family planning. Research method: Qualitative descriptive research method with a case study approach. Results: Midwifery care during Mrs. N from the results of Mrs. N experienced chronic energy deficiency KEK and was given treatment and care according to his needs. Furthermore, on the third visit, the results of Mrs. N no longer experiences chronic energy deficiencies. Birth of Mrs. N was assisted in accordance with the standards for midwifery services for childbirth (APN). Neonatal Visits and Newborn Visits I to III Baby Mrs. N experienced no complications and neither did postpartum visits I to IV. Family planning midwifery care Mrs. N is a 3-month injectable contraceptive. Conclusion: Comprehensive midwifery care has been provided to Mrs. N with KEK is in accordance with obstetric services and there are no complications.